REVITALIZATION OF MODERN FIQH: WELCOMING CURRICULUM RENEWAL IN ISLAMIC EDUCATIONAL INSTITUTIONS - Aini, Sarina (Journal of Learning on History and Social Sciences, 2024)
Objective: This study aims to explore the challenges and strategies for revitalizing the modern fiqh curriculum in Islamic educational institutions to ensure its relevance in addressing contemporary issues. Method: A library research approach was employed, analyzing scientific journal articles and published research reports to gather data on the integration of modern fiqh into the curriculum. Results: The study finds that the integration of modern fiqh in Islamic educational institutions requires updating teaching materials to address contemporary issues, improving teacher competency, and utilizing technology for effective learning. The research highlights the urgency of curriculum revitalization to respond to technological advancements, the digital economy, and other societal challenges. It also identifies resistance to change, limited human resources, and difficulties in harmonizing diverse fiqh views as key barriers. Novelty: This research contributes to the theoretical and practical understanding of modern fiqh curriculum integration, offering a solution-oriented framework to modernize Islamic education and strengthen its applicability in contemporary society.